The hafnium and neodymium isotope composition of seawater in the Atlantic sector of the Southern Ocean - Stichel, Torben; Frank, Martin; Rickli, Jörg Dominik; Haley, Brian A. (Earth and Planetary Science Letters, 2012)
ISSN:0012-821X ISSN:1385-013X